Stages of Women's Social Penetration in Building Intimacy Through the Bumble Application in Yogyakarta - Wulandari, Claudya Putri; Prismarini, Rosalia; Siva, Nur; Putri, Rahma Novita Alim (Formosa Journal of Computer and Information Science, 2025)
The purpose of this study is to analyze and describe the stages of social penetration in women in building intimacy through the Bumble application where women are in control in starting conversations and in relationships. The method used is descriptive research with qualitative methods. Data collection techniques used in this study are observation, interviews and documentation. Interviews were conducted with five informants who are active users of the Bumble online dating application. This study uses a supporting theory, namely social penetration by Altman & Taylor. Based on the results of the study, there are four stages of social penetration that are passed through by active users of the Bumble online dating application, namely orientation, affective exploration, affective exchange and stable exchange. However, not all informants can go through all stages and form new relationships (dating). This happens because in the process of the stages there is a mismatch at each stage, which causes the process of social depentration, or withdrawal. Unwanted factors and mismatches from informants cause the relationship to end, making the relationship unromantic or just friendship